Intradermal Injection of Oxytocin Aggravates Chloroquine-Induced Itch Responses via Activating the Vasopressin-1a Receptor/Nitric Oxide Pathway in Mice - Li, Rulong; Sun, Hua; Zheng, Haotian; Zong, Zhihua; Li, Shengnan; Meng, Tingting; Li, Jing; Liu, Yunfang; Wang, Chao; Li, Jingxin (Frontiers in Pharmacology, 2019)
Oxytocin (OT), a hormone synthesized within the paraventricular nucleus and supraoptic nucleus of the hypothalamus, when given intracerebroventricularly, induces strong scratching behaviors. However, it is not clear whether intradermal injection (ID) of OT elicits itch sensation. Herein, we found that OT did not elicit an itch-scratching response in mice but aggravated chloroquine(CQ)-elicited scratching behavior. Similar to OT, arginine vasopressin (AVP), which is structurally related to OT, also enhanced CQ-induced scratching behavior but did not directly induce considerable scratching behavior in mice. Mechanistically, OT-mediated enhancement of CQ-induced scratching behavior was significantly suppressed by conivaptan (0.05 mg/ml), a vasopressin-1a receptor (V1AR) antagonist and 1400W, inhibitor of inducible nitric oxide synthase (iNOS), but not OT receptor(OTR) antagonist L-368,899 (0.05 mg/ml). Notably, conivaptan also directly decreased CQ-induced scratching. In conclusion, OT plays a role in CQ-induced scratching behavior via V1AR binding events. V1AR antagonists could be used as possible treatments for CQ-induced itch.